2018
DOI: 10.1515/jgth-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

The tower of profinite completions

Abstract: We show that the tower of profinite completions of a nonstrongly complete profinite group continues indefinitely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Notice that the orientation makes Z p a Z p [G]− module, by defining g.x = θ(g)x. We denote this module by Z p (1).…”
Section: Cyclotomic Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that the orientation makes Z p a Z p [G]− module, by defining g.x = θ(g)x. We denote this module by Z p (1).…”
Section: Cyclotomic Orientationmentioning
confidence: 99%
“…In [1] the author presented the infinite tower of profinite completions which is defined as follows: Let G be a nonstrongly complete profinite group and α an ordinal. Denote G 0 = G.…”
Section: Completions Of Higher Ordermentioning
confidence: 99%
“…If α is a limit ordinal, G α = H α where H α = lim →β<α {G β , ϕ γβ }, where ϕ γβ are compatible homomorphisms which are defined for every γ < β. In [2] it is shown that all the groups in this chain are nonstrongly complete, and all the homomorphisms are injections. That makes the chain a strictly increasing chain, which never terminates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the profinite completion we just define, which we can treat as the "first" profinite completion, a nonstrongly complete profinite group admits a series of profinite completions of higher orders, which we denote by G α , and are defined for every ordinal α. These completions of higher order were first introduced in [2] and are built as follows: Let G be a nonstrongly complete profinite group. Denote G = G 0 .…”
Section: Introductionmentioning
confidence: 99%